WHITE SUPREMACY AND STRUCTURAL RACISM IN “THE SHAWSHANK REDEMPTION” BY FRANK DARABONT - Erni Rahmawati; Gustaman Saragih (Universitas Indraprasta PGRI, 2020)
The purpose of this study was to analyze white supremacy and structural racism in the film